Patients with seronegative rheumatoid arthritis have a different phenotype than seropositive patients: A clinical and ultrasound study - Carbonell-Bobadilla, Natalia; Soto-Fajardo, Carina; Amezcua-Guerra, Luis M.; Batres-Marroquín, Ana Beatriz; Vargas, Tania; Hernández-Diazcouder, Adrian; Jiménez-Rojas, Valentin; Medina-García, Ana Cristina; Pineda, Carlos; Silveira, Luis H. (Frontiers in Medicine, 2022)
Introduction: Rheumatoid arthritis (RA) is an inflammatory disease whose clinical phenotype largely depends on the presence of rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA). Seronegative RA appears to be a less severe disease, but this remains controversial. This study aimed to assess whether seronegative patients show a less severe disease than seropositive patients. Methods: A cross-sectional study was conducted on RA outpatients from a single center. Clinical activity scales, laboratory evaluations, and cardiovascular risk scores were assessed. Musculoskeletal ultrasound (US) examinations were performed. Results: One hundred and fourteen patients were enrolled. Eighty-five were seropositive (76% women) and 29 seronegative (93% women). Seropositive patients had a younger age at disease onset (43±14 vs. 54±11; p=0.001) and used sulfasalazine (47% vs. 17%; p=0.004) and glucocorticoids (36% vs. 10%; p=0.007) more frequently. No differences in clinical activity scales and in 10-year cardiovascular risk were observed. Pathological US data were found more frequently in seropositive patients in the 2nd metacarpophalangeal (MCP) joint, both in grayscale (71% vs. 38%; p=0.008) and in power Doppler (PD; 53% vs. 9%; p<0.001); erosions (36% vs. 9%; p=0.020) were also more frequent. We found greater severity of PD signals in the 2nd MCP and 3rd MCP joints of the seropositive patients, while synovitis severity was higher only in the 2nd MCP joints. The percentage of total joints with erosions (9% vs. 1%; p<0.001) and 2nd MCP joints with erosions (25% vs. 7%; p<0.001) was higher in seropositive patients. Conclusion: RA patients show a differentiated phenotype according to their ACPA and RF status. In seronegative patients, RA begins later in life and has a lower requirement for antirheumatic therapies. On US evaluation, seropositive patients show more joint damage, especially in MCP joints. Despite this, long-term cardiovascular risk is similar among RA patients, regardless of their RF and ACPA status.